(untitled) (Research, Society and Development, 2024)
Objective: To map protective factors related to the intestinal microbiota of adult colorectal cancer patients undergoing intravenous chemotherapy. Methodology: Scoping review protocol carried out from January to June 2023, according to the methodology of the Joanna Briggs Institute Evidence Synthesis, in accordance with the PRISMA-ScR checklist, following the steps proposed by the Joanna Briggs Institute: identifying the research question, the relevant studies, selecting the studies and mapping the data. The mnemonic PCC (population, concept and context) determined the research question: What are the protective factors for the intestinal microbiota of adult colorectal cancer patients undergoing intravenous chemotherapy? The acronym PCC was used for data collection, which took place from January to June 2023. The following sources of information were included: Lilacs/Virtual Health Library, Medline/PubMed, Embase and Scopus, Web of Science, COCHRANE, CINAHL and Academic Search Premier, Food Science Source and Food Science and Technology Abstracts, Google Scholar and the CAPES Theses & Dissertations Catalog, published in all languages and with no time limit. The selection was carried out by two independent reviewers and any discrepancies were assessed by a third reviewer. The data was extracted using a collection tool developed by the authors after a pilot test. The data will be presented in accordance with the objectives and research questions. Registration of the review in the Open Science Framework-OSF.IO/Y2U6V.